(untitled) (Intent Research Scientific Journal, 2023)
This article delves into the imperative task of enhancing the role of banks in providing vital financial support to the entrepreneurial sector. Recognizing the crucial role that entrepreneurship plays in economic growth and job creation, the article emphasizes the need for banks to proactively engage in facilitating access to capital and resources for aspiring entrepreneurs. It explores strategies to strengthen the partnership between banks and the entrepreneurial sector, such as tailored financial products, mentorship programs, and streamlined lending processes. The article underscores the potential impact of an empowered entrepreneurial sector on overall economic development and offers insights into overcoming challenges and maximizing the positive contributions of banks to entrepreneurial ventures.